2001
DOI: 10.1067/mjd.2001.112912
|View full text |Cite
|
Sign up to set email alerts
|

Brachioradial pruritus

Abstract: Twenty-one patients seen in a temperate climate who had a clinical diagnosis of brachioradial pruritus are presented. The history and clinical manifestations of the patients indicate that the symptoms were neuralgiform and caused by cumulative sun exposure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
19
0
1

Year Published

2002
2002
2012
2012

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 12 publications
7
19
0
1
Order By: Relevance
“…Histopathologic examination of skin areas with normal appearance were essentially normal, arguing against systemic or subclinical skin abnormalities. Among the differential diagnoses for the skin presentations detected are neurotic excoriations [16], atopic dermatitis, brachioradial pruritis [17], [18], and arthropod bites.…”
Section: Discussionmentioning
confidence: 99%
“…Histopathologic examination of skin areas with normal appearance were essentially normal, arguing against systemic or subclinical skin abnormalities. Among the differential diagnoses for the skin presentations detected are neurotic excoriations [16], atopic dermatitis, brachioradial pruritis [17], [18], and arthropod bites.…”
Section: Discussionmentioning
confidence: 99%
“…Twenty-one of the patients had been included in a previous report ( 1 ). Inclusion criteria: the diagnosis of BRP was made on clinical grounds and based on the patients' description of itching, tingling, and/or a burning sensation on the skin on the lateral aspects of the upper arms (on the dorsal aspect of the forearms and/or on the shoulders).…”
Section: Methodsmentioning
confidence: 99%
“…I Acquired Cl inhibitor deficiency (AAE) is a rare syndrome with features similar to those of hereditary angioedema (HAE), but differirig in its later onset and lack of family history. AAE is characterized by increased consumption of C1 inhibitor associated with lymphoproliferative or malignant disorders, autoimmune or infectious diseases (1,2). In Cl inhibitor deficiency two different skin manifestations can be seen:¡angioedema and erythema marginatum.…”
Section: Rapid Resolution Of Erythema Marginatum After Icatibant In Amentioning
confidence: 99%
“…[1][2][3] For nearly 30 years, BRP was considered to be related to ultraviolet (UV) irradiation because UV exposure worsens the symptom. 2,[4][5][6][7][8][9][10][11][12][13][14] As early as 1983, Heyl 3 proposed that BRP may be caused by nerve injury in the cervical spine or by nerve compression (NC). Several recent studies have suggested that BRP may result from cervical spine lesions such as radiculopathy, disk herniation, osteophytes, or spinal neoplasms.…”
mentioning
confidence: 99%